Carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas and preparation method of carbon-doped boron nitride

By introducing carbon atoms into the boron nitride structure to form carbon doped boron nitride, using its multi-active sites and porous structure, the problem of removing heavy metal pollutants in high-temperature flue gas is solved, and efficient and rapid heavy metal adsorption effect is achieved.

CN119549107APending Publication Date: 2025-03-04SHENYANG AEROSPACE UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510047741.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove heavy metal contaminants in high-temperature flue gases, especially heavy metal contaminants generated when incineration of solid waste.

Method used

By introducing carbon atoms into the boron nitride structure, carbon doped boron nitride is formed, and its multi-active sites and porous structure are used to achieve the synergistic effect of physical adsorption and chemical adsorption, and heavy metal ions in the flue gas are removed.

Benefits of technology

It realizes rapid and effective adsorption of heavy metal substances such as Cd, Pd, Zn and Cu in high-temperature flue gas, significantly reducing the formation of heavy metal particles and increasing the specific gravity of the adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549107A_ABST
    Figure CN119549107A_ABST
Patent Text Reader

Abstract

The invention provides carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas and a preparation method of the carbon-doped boron nitride, and belongs to the technical field of combined control of various atmospheric pollutants. According to the carbon-doped boron nitride, more carbon atoms are introduced into a boron nitride structure through carbon doping, the carbon atoms replace part of boron atoms, and the original structure of the boron nitride is changed; compared with boron nitride, the carbon-doped boron nitride has the advantages that the atom proportion of carbon atoms in the carbon-doped boron nitride is increased by 2.92%-58.22%, heavy metals in the flue gas are removed through the synergistic effect of physical adsorption and chemical adsorption, and simultaneous adsorption of more than one heavy metal in the flue gas is realized after 5 minutes. Compared with activated carbon as a heavy metal adsorbent, the preparation method is simple, the blank of adsorption capacity in high-temperature flue gas is filled, heavy metal substances such as Cd, Pd, Zn and Cu can be adsorbed at the same time, and the adsorbent is successfully applied to adsorption of heavy metal ions in the high-temperature flue gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of joint control of various air pollutants, and in particular relates to a carbon-doped boron nitride for effectively absorbing heavy metals in flue gas and a preparation method thereof. Background Art

[0002] Removing heavy metal pollutants from flue gas is still a very serious problem. The Opinions on Further Strengthening the Prevention and Control of Heavy Metal Pollution clearly pointed out that it is necessary to strengthen the clean production transformation of key industry enterprises.

[0003] Strengthen the development and application of clean production processes in key industries. Heavy metal components in flue gas come from many sources, a large part of which comes from the incineration of solid waste. How to reasonably, efficiently and cleanly control heavy metal pollutants generated by the incineration of solid waste has become an important condition for promoting the peaceful and stable development of my country's ecological environment.

[0004] Studies have shown that boron nitride has excellent adsorption properties for heavy metals such as cadmium, lead, copper and iron. In most studies, the porous structure of boron nitride is used to adsorb heavy metals in the gas. Carbon-doped boron nitride is a modified boron nitride. This material is in powder form and has more active sites. Compared with ordinary boron nitride powder, it has a stronger adsorption capacity for heavy metals.

[0005] At present, some studies have been conducted on the adsorption of heavy metals in flue gas by boron nitride, but few studies have been conducted on the adsorption of heavy metals in flue gas by carbon-doped boron nitride. In addition, in today's world where energy conservation and emission reduction are advocated, there are no reports on the proposal of a new type of adsorbent that uses active sites and porous structures to simultaneously adsorb heavy metal ions.

[0006] In summary, developing a new adsorbent material that can adsorb heavy metal substances in high-temperature flue gas is an important issue that needs to be solved urgently. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas and a preparation method thereof. The carbon-doped boron nitride has multiple active sites and a porous structure, and can synergistically remove heavy metal ions such as Cd, Pd and Zn in flue gas, thereby solving the problems caused by heavy metal pollutants in flue gas.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] The present invention provides a carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas. More carbon atoms are introduced into the boron nitride structure by carbon doping, and carbon atoms replace part of boron atoms, thereby changing the original structure of the boron nitride. Compared with boron nitride, the atomic ratio of carbon atoms in the carbon-doped boron nitride is increased by 2.92%-58.22%, and physical adsorption and chemical adsorption synergistically remove heavy metal ions in flue gas, and more than one heavy metal in flue gas can be simultaneously adsorbed after 5 minutes.

[0010] Doping and introducing carbon atoms will destroy the crystal structure of boron nitride and replace some of the boron atoms, increasing the polarity and forming new carbon-nitrogen bonds and carbon-hydrogen bonds. At the same time, incomplete substitution will also occur, that is, after the boron-nitrogen bond is broken, no carbon-nitrogen bond is formed, but more amino groups are formed. The newly formed carbon-hydrogen bonds and amino groups will increase the active sites for binding to metal ions and enhance the chemical adsorption performance.

[0011] Furthermore, the flue gas is high-temperature flue gas, and the heavy metals include one or more of Cd, Pd, Zn and Cu.

[0012] The present invention also provides a method for preparing the carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas, comprising the following steps:

[0013] Step 1: Nitrogen source melamine (C3H6N6), boron source boric acid (H3BO3) and carbon source glucose (C6H 12 O6) Mix and stir evenly;

[0014] Step 2: Add deionized water to the three substances that are evenly mixed and stirred, and mix them thoroughly to obtain a solution containing particulate matter;

[0015] Step 3: placing the solution of the granular substance in a stirrer and stirring to obtain a clear solution;

[0016] Step 4: cooling the clear solution for crystallization to obtain a crystalline product;

[0017] Step 5: Filter the crystallized product by suction, and the obtained solid precipitate is the precursor, which is then dried;

[0018] Step 6: calcining the dried precursor under the protection of an inert gas to obtain carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas.

[0019] Furthermore, the mass ratio of melamine, boric acid and glucose in step 1 is 1:1:(0.5-2).

[0020] Preferably, the mass ratio of melamine, boric acid and glucose in step 1 is 1:1:1.

[0021] Furthermore, the thorough mixing in step 2 is performed using an ultrasonic device;

[0022] In step 3, the stirrer is a constant temperature water bath stirrer or a magnetic stirrer.

[0023] Furthermore, in step 4, the cooling crystallization is carried out at room temperature of 20°C-30°C, and the cooling time is ≥12h.

[0024] Furthermore, in step 5, a filter membrane is used for suction filtration, and an oven is used for drying.

[0025] Furthermore, in step 6, a tubular furnace is used for calcination, an inert gas is introduced before calcination to exclude other gases, the calcination temperature is 900° C.-1350° C., and the calcination time is 3 h-5 h;

[0026] The inert gas is nitrogen.

[0027] The present invention also provides an application of the carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas, which is used as an adsorbent to adsorb heavy metals in flue gas.

[0028] Furthermore, the application of carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas adopts a double-temperature-section tubular furnace to simulate the heavy metals in the flue gas by adding heavy metal salts. The heavy metal salts are placed in the front section of the tubular furnace, and the incineration temperature is set to 900°C±50°C. The carbon-doped boron nitride adsorbent is placed in the rear section of the tubular furnace, and the temperature is set to 400°C±10°C.

[0029] Preferably, the boric acid (H3BO3) and melamine (C3H6N6) and glucose (C6H 12 O6) in a mass ratio of 1:1:1; add 1000 ml of deionized water at an ambient temperature of 20°C to 30°C;

[0030] Preferably, the mixture in step 2 is subjected to ultrasonic stirring for 10 min to obtain a granular precipitate;

[0031] Preferably, the stirring time in step 3 is 2 h, the stirring temperature is 85° C., and a clear solution is obtained;

[0032] Preferably, the clear solution obtained in step 4 is allowed to stand at room temperature of 20° C. to 30° C. and cooled for 12 hours to obtain a crystalline product;

[0033] Preferably, in step 5, a 45 μm filter membrane is used for suction filtration, and the obtained precursor is dried in an oven at 105° C. for 24 hours;

[0034] Preferably, in step 6, the protective gas nitrogen is used at a flow rate of 200 mL / min, and ventilation is performed at a flow rate of 200 mL / min for 10 min before calcination to ensure that there is no other gas in the tube.

[0035] Beneficial effects of the present invention:

[0036] The present invention provides a carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas and a preparation method thereof. The carbon-doped boron nitride has multiple active sites and a porous structure. Compared with activated carbon, the preparation method of the carbon-doped boron nitride as a heavy metal adsorbent is relatively simple, and the carbon-doped boron nitride fills the gap in adsorption capacity in high-temperature flue gas and can simultaneously adsorb heavy metal substances such as Cd, Pd, Zn and Cu.

[0037] In actual application, the volatilized heavy metal gas reacts with the carbon-doped boron nitride adsorbent prepared by the present invention, the generated flue gas is significantly reduced, and the specific gravity of the adsorbent is increased, which significantly reduces the formation of heavy metal particles. The adsorbent is successfully used in high-temperature flue gas.

[0038] It should be noted that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is an X-ray photoelectron spectrum (XPS) diagram of carbon-doped boron nitride in Example 1 of the present invention;

[0040] Figure 2 is an X-ray photoelectron spectrum (XPS) diagram of carbon-doped boron nitride in Example 2 of the present invention;

[0041] Figure 3 is an X-ray photoelectron spectrum (XPS) diagram of carbon-doped boron nitride in Example 3 of the present invention;

[0042] Figure 4 This is an X-ray photoelectron spectrum (XPS) diagram of carbon-doped boron nitride in Comparative Example 1 of the present invention;

[0043] Figure 5 This is a nitrogen adsorption-desorption curve diagram of carbon-doped boron nitride in Example 1 of the present invention;

[0044] Figure 6 This is a nitrogen adsorption-desorption curve diagram of carbon-doped boron nitride in Example 2 of the present invention;

[0045] Figure 7 This is a nitrogen adsorption-desorption curve diagram of carbon-doped boron nitride in Example 3 of the present invention;

[0046] Figure 8 This is the nitrogen adsorption-desorption curve of boron nitride in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0047] The present invention is described in detail below in conjunction with the embodiments. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples of systems consistent with some aspects of the present invention as detailed in the appended claims.

[0048] In response to the problems of excessive heavy metal content, high temperature, and high flue gas flow rate in solid waste flue gas, the present invention has developed a preparation scheme for an adsorbent that can adsorb heavy metals in high-temperature flue gas. It can simultaneously adsorb heavy metal substances such as Cd, Pb and Zn, and also makes up for the insufficient adsorption capacity of activated carbon at high temperatures.

[0049] In the application of carbon-doped boron nitride and comparative boron nitride in the embodiments of the present invention, carbon-doped boron nitride and boron nitride are used as adsorbents to adsorb heavy metals in flue gas, respectively. Heavy metal salts are added to simulate heavy metals in flue gas. Calcination is started in a double-temperature-section tubular furnace. The front-section calcination temperature is 900°C ± 50°C, and the rear-section calcination temperature is (300°C - 600°C) ± 10°C. After setting the program, the front-section temperature zone is opened first, and the rear-section temperature zone is opened after calculating the time, so that the temperature zones at both ends are heated to the set temperature at the same time. The weighed heavy metal salt is placed in a container and pushed into the front-section temperature zone. At the same time, multiple groups of adsorbent samples (0.2 g per group) are placed in the rear-section temperature zone of the tubular furnace, and the adsorption time of each group of samples is controlled by the sampling interval.

[0050] Two scrubbing bottles are set at the tail end of the device. The front scrubbing bottle is mixed with deionized water at a ratio of 5% by sodium hydroxide, and the rear scrubbing bottle is mixed with deionized water at a ratio of 10% by nitric acid to neutralize the heavy metal flue gas, and finally the neutralized flue gas is discharged.

[0051] The carbon-doped boron nitride adsorbent placed at the rear end of the double-temperature tube furnace reacts with volatile heavy metal substances and eventually adsorbs a large amount of heavy metal substances in the flue gas. The unadsorbed flue gas is neutralized by different acid and alkali scrubbing bottles and then discharged into the atmosphere, thus avoiding heavy metal pollution to the air.

[0052] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the claims.

[0053] In order to better illustrate the technical means and product effects of the present invention, the following embodiments of the present invention are described.

[0054] Example 1

[0055] A carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas, wherein more carbon atoms are introduced into the boron nitride structure by carbon doping, and carbon atoms replace part of the boron atoms, thereby changing the original structure of the boron nitride; compared with boron nitride, the atomic ratio of carbon atoms in the carbon-doped boron nitride is increased by 58.22%, the polarity is increased, the number of active sites is increased, and the heavy metal ions in the flue gas are removed by synergistic action of physical adsorption and chemical adsorption, and more than one heavy metal in the flue gas can be adsorbed simultaneously in 5 minutes;

[0056] like Figure 1 The XPS image of carbon-doped boron nitride in this embodiment is shown. It can be seen that B1s (199.5 eV), N 1s (409.5 eV), C 1s (297.5 eV) and O1s (544.5 eV) have atomic proportions of 21.65%, 31.83%, 24.35% and 18.67%, respectively. Among them, the atomic proportion of C atoms is 58.22% higher than that of ordinary boron nitride in Comparative Example 1, which further indicates that carbon-doped boron nitride has more active sites.

[0057] A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas comprises the following steps:

[0058] Step 1: Mix 13g of melamine C3H6N6, 13g of boric acid H3BO3 and 13g of glucose C6H 12 O6 mix and stir evenly;

[0059] Step 2: Add 1000 ml of deionized water to the three substances that are evenly mixed, and fully mix the three substances by an ultrasonic device to obtain a solution containing particulate matter;

[0060] Step 3: placing the solution of the granular substance in a water bath stirrer and stirring for 2 h, wherein the temperature is set to 85° C. and the rotation speed is set to 400 rpm to obtain a clear solution;

[0061] Step 4: The clarified solution was allowed to stand at room temperature of 20°C-30°C for 12 hours to obtain a crystalline product;

[0062] Step 5: The crystallized product is filtered using a 45 μm filter membrane, and the obtained solid precipitate precursor is placed in an oven at 105° C. and dried for 24 hours;

[0063] Step 6: The dried precursor is placed in a tubular calcination furnace, and nitrogen is used as a protective atmosphere at a flow rate of 200 mL / min. Before calcination, ventilation is performed at a flow rate of 200 mL / min for 10 minutes to ensure that there is no other gas in the tube; the calcination time is 5 hours, and the calcination temperature is 900°C, and finally carbon-doped boron nitride for effective adsorption of heavy metals in flue gas is obtained.

[0064] An application of carbon-doped boron nitride that effectively adsorbs heavy metals in flue gas, using it as an adsorbent to analyze its adsorption performance for heavy metals in high-temperature flue gas;

[0065] Nitrogen was used as the gas environment with a gas flow rate of 1 L / min, and heavy metal salts were added to the front section of the double-temperature section tubular furnace to simulate heavy metals in the flue gas. The specific components were Zncl2, Cucl2, Cdcl2 and Pbcl2, and the addition amount was 5 g each. The samples were incinerated in the front section of the double-temperature section tubular furnace at a temperature of 900°C ± 50°C. Five groups (0.2 g per group) of carbon-doped boron nitride powder samples of this embodiment were placed in the second half of the double-temperature section tubular furnace, and the temperature was set to 400°C ± 10°C. The front section of the tubular furnace was first heated, and the front and rear sections of the tubular furnace were heated at the same rate. After calculating the time for the front and rear sections to reach the set temperature at the same time, the second half of the tubular furnace was heated after the calculated time. Then, the container containing the heavy metal salt is placed in the front half of the tube furnace. When the set temperature of 400°C±10°C is reached in the rear section of the tube furnace, it is recorded as 0min. A group of samples are taken at 5min, 10min, 20min, 30min and 40min to analyze the effect of adsorption time on adsorption capacity. The incineration is carried out in a nitrogen atmosphere, and the experimental tail gas is treated with 10% nitric acid HNO3 and 5% sodium hydroxide NaOH. After the experiment, the heavy metal content in the carbon-doped boron nitride adsorbent is measured using an inductively coupled plasma spectrometer (ICP). As shown in Table 1, the adsorption amount (mg / g) of heavy metals by the carbon-doped boron nitride adsorbent at different incineration times in a nitrogen atmosphere.

[0066] Table 1 Adsorption amount of heavy metals by carbon-doped boron nitride adsorbent at different times (mg / g)

[0067] heavy metal 5min 10min 20min 30min 40min Zn 18.34 37.06 69.55 72.53 85.94 Cd 33.62 68.58 74.36 94.35 108.9 Pb 38.74 85.15 102.3 114.59 168.0 Cu 8.07 21.55 45.24 75.59 80.81

[0068] It can be seen from Table 1 that at the same temperature, carbon-doped boron nitride as an adsorbent has a faster adsorption rate. It can simultaneously adsorb Cd, Pd, Zn and Cu in 5 minutes, and the adsorption amount increases with the increase of adsorption time. The increase of adsorption time can increase the collection efficiency of the adsorbent for heavy metals.

[0069] Example 2

[0070] A carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas, wherein more carbon atoms are introduced into the boron nitride structure through carbon doping, and carbon atoms replace part of the boron atoms, thereby changing the original structure of the boron nitride; compared with boron nitride, the atomic ratio of carbon atoms in the carbon-doped boron nitride is increased by 4.94%, the polarity is increased, the number of active sites is increased, and the synergistic effect of physical adsorption and chemical adsorption is used to remove heavy metal ions in flue gas, and more than one heavy metal in flue gas can be adsorbed simultaneously in 5 minutes;

[0071] like Figure 2 The XPS image of carbon-doped boron nitride in this embodiment is shown. It can be seen that B1s (199.5 eV), N 1s (409.5 eV), C 1s (297.5 eV) and O1s (544.5 eV) have atomic proportions of 37.66%, 30.66%, 16.15% and 13.82%, respectively. The atomic proportion of C atoms is 4.94% higher than that of ordinary boron nitride in Comparative Example 1, which further indicates that carbon-doped boron nitride has more active sites.

[0072] A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas comprises the following steps:

[0073] Step 1: Mix 13g of melamine C3H6N6, 13g of boric acid H3BO3 and 26g of glucose C6H 12 O6 mix and stir evenly;

[0074] Step 2: Add 1000 ml of deionized water to the three substances that are evenly mixed, and fully mix the three substances by an ultrasonic device to obtain a solution containing particulate matter;

[0075] Step 3: placing the solution of the granular substance in a water bath stirrer and stirring for 2 h, wherein the temperature is set to 85° C. and the rotation speed is set to 400 rpm to obtain a clear solution;

[0076] Step 4: The clarified solution was allowed to stand at room temperature of 20°C-30°C for 12 hours to obtain a crystalline product;

[0077] Step 5: The crystallized product is filtered using a 45 μm filter membrane, and the obtained solid precipitate precursor is placed in an oven at 105° C. and dried for 24 hours;

[0078] Step 6: The dried precursor is placed in a tubular calcining furnace, and nitrogen is used as a protective atmosphere at a flow rate of 200 mL / min. Before calcination, ventilation is performed at a flow rate of 200 mL / min for 10 minutes to ensure that there is no other gas in the tube; the calcination time is 4 hours, and the calcination temperature is 1200°C, and finally carbon-doped boron nitride is obtained for effective adsorption of heavy metals in flue gas.

[0079] An application of carbon-doped boron nitride that effectively adsorbs heavy metals in flue gas, using it as an adsorbent to analyze its adsorption performance for heavy metals in high-temperature flue gas;

[0080] Nitrogen was used as the gas environment with a gas flow rate of 1 L / min, and heavy metal salts were added to the front section of the double-temperature section tubular furnace to simulate heavy metals in the flue gas. The specific components were Zncl2, Cucl2, Cdcl2 and Pbcl2, and the addition amount was 5 g each. The samples were incinerated in the front section of the double-temperature section tubular furnace at a temperature of 900°C ± 50°C. Five groups (0.2 g per group) of carbon-doped boron nitride powder samples of this embodiment were placed in the second half of the double-temperature section tubular furnace, and the temperature was set to 400°C ± 10°C. The front section of the tubular furnace was first heated, and the front and rear sections of the tubular furnace were heated at the same rate. After calculating the time for the front and rear sections to reach the set temperature at the same time, the second half of the tubular furnace was heated after the calculated time. Then, the container containing the heavy metal salt is placed in the front half of the tube furnace. When the set temperature of 400°C±10°C is reached in the rear section of the tube furnace, it is recorded as 0min. A group of samples are taken at 5min, 10min, 20min, 30min and 40min to analyze the effect of adsorption time on adsorption capacity. The incineration is carried out in a nitrogen atmosphere, and the experimental tail gas is treated with 10% nitric acid HNO3 and 5% sodium hydroxide NaOH. After the experiment, the heavy metal content in the carbon-doped boron nitride adsorbent is measured using an inductively coupled plasma spectrometer (ICP). As shown in Table 2, the adsorption amount (mg / g) of heavy metals by the carbon-doped boron nitride adsorbent after incineration for different times in a nitrogen atmosphere.

[0081] Table 2 Adsorption amount of heavy metals by carbon-doped boron nitride adsorbent at different times (mg / g)

[0082] heavy metal 5min 10min 20min 30min 40min Zn 12.59 24.78 60.35 63.11 65.06 Cd 22.34 57.44 69.68 75.34 79.64 Pb 24.16 70.83 87.61 90.28 99.64 Cu 6.09 12.04 39.78 46.26 51.03

[0083] It can be seen from Table 2 that at the same temperature, carbon-doped boron nitride has a faster adsorption rate as an adsorbent. It can simultaneously adsorb Cd, Pd, Zn and Cu in 5 minutes, and the adsorption amount increases with the increase of adsorption time. The increase of adsorption time can increase the collection efficiency of the adsorbent for heavy metals.

[0084] Example 3

[0085] A carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas, wherein more carbon atoms are introduced into the boron nitride structure by carbon doping, and carbon atoms replace part of the boron atoms, thereby changing the original structure of the boron nitride; compared with boron nitride, the atomic ratio of carbon atoms in the carbon-doped boron nitride is increased by 2.92%, the polarity is increased, the number of active sites is increased, and the synergistic effect of physical adsorption and chemical adsorption is used to remove heavy metal ions in flue gas, and more than one heavy metal in flue gas can be adsorbed simultaneously in 5 minutes;

[0086] like Figure 3 The XPS image of carbon-doped boron nitride in this embodiment is shown. It can be seen that B1s (199.5 eV), N 1s (409.5 eV), C 1s (297.5 eV) and O1s (544.5 eV) have atomic proportions of 38.83%, 39.39%, 15.84% and 11.81%, respectively. The atomic proportion of C atoms is 2.92% higher than that of ordinary boron nitride in Comparative Example 1, which further indicates that carbon-doped boron nitride has more active sites.

[0087] A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas comprises the following steps:

[0088] Step 1: Mix 13g of melamine C3H6N6, 13g of boric acid H3BO3 and 6.5g of glucose C6H 12 O6 mix and stir evenly;

[0089] Step 2: Add 1000 ml of deionized water to the three substances that are evenly mixed, and fully mix the three substances by an ultrasonic device to obtain a solution containing particulate matter;

[0090] Step 3: placing the solution of the granular substance in a water bath stirrer and stirring for 2 h, wherein the temperature is set to 85° C. and the rotation speed is set to 400 rpm to obtain a clear solution;

[0091] Step 4: The clarified solution was allowed to stand at room temperature of 20°C-30°C for 12 hours to obtain a crystalline product;

[0092] Step 5: The crystallized product is filtered using a 45 μm filter membrane, and the obtained solid precipitate precursor is placed in an oven at 105° C. and dried for 24 hours;

[0093] Step 6: The dried precursor is placed in a tubular calcining furnace, and nitrogen is used as a protective atmosphere at a flow rate of 200 mL / min. Before calcination, ventilation is performed at a flow rate of 200 mL / min for 10 minutes to ensure that there is no other gas in the tube; the calcination time is 3 hours, and the calcination temperature is 1350°C, and finally carbon-doped boron nitride is obtained for effectively adsorbing heavy metals in flue gas.

[0094] An application of carbon-doped boron nitride that effectively adsorbs heavy metals in flue gas, using it as an adsorbent to analyze its adsorption performance for heavy metals in high-temperature flue gas;

[0095] Nitrogen was used as the gas environment with a gas flow rate of 1 L / min, and heavy metal salts were added to the front section of the double-temperature section tubular furnace to simulate heavy metals in the flue gas. The specific components were Zncl2, Cucl2, Cdcl2 and Pbcl2, and the addition amount was 5 g each. The samples were incinerated in the front section of the double-temperature section tubular furnace at a temperature of 900°C ± 50°C. Five groups (0.2 g per group) of carbon-doped boron nitride powder samples of this embodiment were placed in the second half of the double-temperature section tubular furnace, and the temperature was set to 400°C ± 10°C. The front section of the tubular furnace was first heated, and the front and rear sections of the tubular furnace were heated at the same rate. After calculating the time for the front and rear sections to reach the set temperature at the same time, the second half of the tubular furnace was heated after the calculated time. Then, the container containing the heavy metal salt is placed in the front half of the tube furnace. When the set temperature of 400°C±10°C is reached in the rear section of the tube furnace, it is recorded as 0min. A group of samples are taken at 5min, 10min, 20min, 30min and 40min to analyze the effect of adsorption time on adsorption capacity. The incineration is carried out in a nitrogen atmosphere, and the experimental tail gas is treated with 10% nitric acid HNO3 and 5% sodium hydroxide NaOH. After the experiment, the heavy metal content in the carbon-doped boron nitride adsorbent is measured using an inductively coupled plasma spectrometer (ICP). As shown in Table 3, the adsorption amount (mg / g) of heavy metals by the carbon-doped boron nitride adsorbent is determined after incineration for different times in a nitrogen atmosphere.

[0096] Table 3 Adsorption amount of heavy metals by carbon-doped boron nitride adsorbent at different times (mg / g)

[0097] heavy metal 5min 10min 20min 30min 40min Zn 1.03 17.86 59.36 63.48 64.85 Cd 0.899 12.86 66.42 76.35 80.94 Pb 0.94 11.45 82.55 99.64 108.34 Cu 0.72 3.29 39.56 43.06 47.61

[0098] It can be seen from Table 3 that at the same temperature, carbon-doped boron nitride has a faster adsorption rate as an adsorbent. It can simultaneously adsorb Cd, Pd, Zn and Cu in 5 minutes, and the adsorption amount increases with the increase of adsorption time. The increase of adsorption time can increase the collection efficiency of the adsorbent for heavy metals.

[0099] Comparative Example 1

[0100] A boron nitride, such as Figure 4 Shown is the XPS image of boron nitride in this comparative example, from which it can be seen that B1s (199.5 eV), N1s (409.5 eV), C 1s (297.5 eV) and O1s (544.5 eV) account for 40.27%, 29.46%, 15.39% and 12.88% of the atoms respectively.

[0101] A method for preparing boron nitride, which differs from Example 3 in that carbon doping is not performed, comprises the following steps:

[0102] Step 1: Mix 13 g of melamine C3H6N6 and 13 g of boric acid H3BO3 and stir evenly;

[0103] Step 2: Add 1000 ml of deionized water to the three substances that are evenly mixed and stirred, and fully mix the three substances by an ultrasonic device to obtain a solution containing flocculent substances;

[0104] Step 3: Place the flocculent solution in a water bath stirrer and stir for 2 hours, wherein the temperature is set to 85°C and the speed is set to 400 rpm to obtain a clear solution;

[0105] Step 4: The clarified solution was allowed to stand at room temperature of 20°C-30°C for 12 hours to obtain a crystalline product;

[0106] Step 5: Filter the crystallized product and dry the obtained solid precipitate precursor in an oven at 105° C. for 24 hours;

[0107] Step 6: Place the dried precursor in a tubular calcining furnace, use nitrogen as a protective atmosphere, and calcine at a flow rate of 200 mL / min. Before calcining, ventilate at a flow rate of 200 mL / min for 10 minutes to ensure that there is no other gas in the tube; the calcination time is 5 hours, and the calcination temperature is 900°C, and finally undoped ordinary boron nitride is obtained.

[0108] A boron nitride is used to adsorb heavy metals in high-temperature flue gas. It is used as an adsorbent to analyze its adsorption performance for heavy metals in high-temperature flue gas, and is compared and analyzed with Examples 1, 2 and 3 of the present invention;

[0109] Nitrogen was used as the gas environment with a gas flow rate of 1 L / min, and heavy metal salts were added to the front section of the double-temperature section tubular furnace to simulate the heavy metals in the flue gas. The specific components were Zncl2, Cucl2, Cdcl2 and Pbcl2, and the addition amount was 5 g each. They were incinerated in the front section of the double-temperature section tubular furnace at a temperature of 900°C ± 50°C. Five groups (0.2 g each) of boron nitride powder samples of this comparative example were placed in the second half of the double-temperature section tubular furnace, and the temperature was set to 400°C ± 10°C. The front section of the tubular furnace was first heated, and the front and rear sections of the tubular furnace were heated at the same rate. After calculating the time for the front and rear sections to reach the set temperature at the same time, the second half of the tubular furnace was heated again after the time was calculated. The temperature was raised, and then the container containing the heavy metal salt was placed in the front half of the tube furnace. When the set temperature of 400°C±10°C was reached in the rear section of the tube furnace, it was recorded as 0min. A group of samples were taken at 5min, 10min, 20min, 30min and 40min to analyze the effect of adsorption time on adsorption capacity. The incineration was carried out under a nitrogen atmosphere, and the experimental tail gas was treated with 10% nitric acid HNO3 and 5% sodium hydroxide NaOH. After the experiment, the heavy metal content in the boron nitride adsorbent was measured using an inductively coupled plasma spectrometer (ICP). As shown in Table 4, the adsorption amount (mg / g) of heavy metals by the boron nitride adsorbent at different incineration times under a nitrogen atmosphere.

[0110] Table 4 Adsorption amount of heavy metals by boron nitride adsorbent at different times (mg / g)

[0111] heavy metal 5min 10min 20min 30min 40min Zn / 1.045 60.57 61.90 63.56 Cd / / 74.36 72.45 73.04 Pb / / 91.30 93.56 94.82 Cu / 0.393 43.23 40.06 43.01

[0112] As can be seen from Table 4, at the same temperature, compared with the carbon-doped boron nitride of the present invention, the ordinary boron nitride adsorbent of this comparative example has a slower adsorption rate, starts to adsorb after 10 minutes, and only achieves simultaneous adsorption of two metals, Zn and Cu. However, as the adsorption time increases, although Cd, Pd, Zn and Cu can be adsorbed simultaneously after 20 minutes, the adsorption amount is lower than that of the carbon-doped boron nitride of the present invention, and there is no obvious improvement in the adsorption amount after 20 minutes, and the collection efficiency of the adsorbent for heavy metals cannot be increased by increasing the adsorption time.

[0113] Adsorption performance analysis

[0114] The specific surface area of ​​the ordinary boron nitride in Comparative Example 1 was 1100.748 m 2 / g, the specific surface areas of carbon-doped boron nitride in Example 1, Example 2 and Example 3 are 598.760 m 2 / g, 1061.460m 2 / g and 865.006m 2 / g, such as Figure 5 , Figure 6 , Figure 7 and Figure 8 As shown, they are nitrogen adsorption-desorption curves of Example 1, Example 2, Example 3 and Comparative Example 1, respectively. It can be seen that the theoretical adsorption capacity of ordinary boron nitride is higher than that of carbon-doped boron nitride, which mainly reflects the physical adsorption performance. However, combined with the heavy metal adsorption data in Tables 1, 2, 3 and 4 in Example 1, Example 2, Example 3 and Comparative Example 1, it can be seen that the carbon-doped boron nitride of the present invention has better adsorption performance, which indicates that after the carbon-doped boron nitride introduces carbon atoms, it has more active sites. For heavy metals in flue gas, in addition to the physical adsorption of the porous structure, the chemical adsorption of the active sites is more used to improve the overall adsorption performance. Therefore, the adsorption performance is better than that of ordinary boron nitride.

[0115] In summary, compared with the existing boron nitride adsorbent, the carbon-doped boron nitride of the present invention not only has the physical adsorption performance reflected by the porous structure, but also has more active sites, exhibits better chemical adsorption performance, thereby improving the overall adsorption performance, and can achieve rapid and effective capture of heavy metals in high-temperature flue gas.

Claims

1. A carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas, characterized in that: More carbon atoms are introduced into the boron nitride structure by carbon doping, and carbon atoms replace part of the boron atoms, thereby changing the original structure of boron nitride. Compared with boron nitride, the atomic ratio of carbon atoms in the carbon-doped boron nitride is increased by 2.92%-58.22%, and physical adsorption and chemical adsorption work synergistically to remove heavy metals in flue gas, achieving simultaneous adsorption of more than one heavy metal in flue gas after 5 minutes.

2. A carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 1, characterized in that: The flue gas is high-temperature flue gas, and the heavy metals include one or more of Cd, Pd, Zn and Cu.

3. A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Mix and stir the nitrogen source melamine, the boron source boric acid and the carbon source glucose evenly; Step 2: Add deionized water to the three substances that are evenly mixed and stirred, and mix them thoroughly to obtain a solution containing particulate matter; Step 3: placing the solution of the granular substance in a stirrer and stirring to obtain a clear solution; Step 4: cooling the clarified solution to crystallize to obtain a crystalline product; Step 5: Filter the crystallized product by suction, and the obtained solid precipitate is the precursor, which is then dried; Step 6: calcining the dried precursor under the protection of an inert gas to obtain carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas.

4. A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 3, characterized in that: The mass ratio of melamine, boric acid and glucose in step 1 is 1:1:(0.5-2).

5. A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 4, characterized in that: The mass ratio of melamine, boric acid and glucose in step 1 is 1:1:

1.

6. A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 3, characterized in that: In step 4, the cooling crystallization is carried out at room temperature of 20°C-30°C, and the cooling time is ≥12h.

7. A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 3, characterized in that: In step 5, a filter membrane is used for suction filtration, and an oven is used for drying.

8. A method for preparing carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 3, characterized in that: In step 6, a tubular furnace is used for calcination. Before calcination, an inert gas is introduced to exclude other gases. The calcination temperature is 900° C.-1350° C., and the calcination time is 3 h-5 h. The inert gas is nitrogen.

9. An application of carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 1 or 2, characterized in that: The carbon-doped boron nitride is used as an adsorbent to adsorb heavy metals in flue gas.

10. The use of carbon-doped boron nitride for effectively adsorbing heavy metals in flue gas as claimed in claim 9, characterized in that: A double-temperature-section tubular furnace is used to simulate heavy metals in flue gas by adding heavy metal salts. Heavy metal salts are placed in the front section of the tubular furnace, and the incineration temperature is set to 900°C±50°C. Carbon-doped boron nitride adsorbent is placed in the rear section of the tubular furnace, and the temperature is set to 400°C±10°C.

Citation Information

Cited By

  • Adsorption treatment system for heavy metal particles in waste incineration flue gas

    CN121288457A